(untitled) (Research, Society and Development, 2021)
Manual lymphatic drainage (DLM), consists of a maneuver technique used in physiotherapy treatments, in order to smoothly direct and increase lymphatic flow. The procedure is considered an alternative for the treatment of edema in the lower limbs, mostly caused by aging and insufficiencies (cardiac, hepatic, lymphatic, renal and venous). In this sense, the objective is to present the benefits of treating lower limb edema through MLD. For this purpose, bibliographic data extracted from articles in Portuguese and English published between 1995-2019 in the databases: LILACS, Scielo, MEDLINE and BVS were used. Using the words “edema”, “lymphatic drainage” and “lower limbs”, 52 articles were obtained. Among them, 8 fit the criteria of this study and were analyzed. The studies presented the conditions of patients before and after therapy. It was found in the articles that all patients had circulatory or lymphatic involvement that generated edema. As a result, they underwent stimulation and evacuation of lymph nodes, following movements with rhythmic pressure, slow and smooth, in addition to measures of compression on the affected region. This therapy proved to be efficient in the treatment of dermatofibrosis, phlebitis, chronic venous disease, iceloid fibroedema and lymphedemas; promoting edema reduction and pain relief.